Purificação, caracterização e avaliação de atividade antifúngica e citotóxica da lectina de casca de Genipa americana (Jenipapo) - Costa, Ricardo Bezerra (2018)
The use of the genipap culture Genipa américana presents great economic potential and in folk medicine and so on in case of suspension of the presence of the bioactive compounds present in the species. Among these, we can cite a presence of lectins, a narrow class of protein with medical and biotechnological importance due to itsantifungal, antitumor, mitogen and insecticideactivities, and as a potent biological marker, due to its ability to specifically bind to carbohydrates. We consider the importance shown by the vegetable city species, the present work by the objective, as a citation, as for example, the cytocommands and antimicrobials. The bark extract was prepared in 50 mM Tris-Hcl pH 8.0 buffer under constant stirring for 12 h at 4 ° C. Saline precipitation was then performed using ((NH4) 2 SO4). A fraction that presented higher hemagglutinating activity (F1-20%) was submitted to the exclusion chromatography (Sephacryl S-100) for possible isolation. By a single chromatographic step to isolated a lectin (GaBL) and by means of SDS-PAGE (10%) it was observed that GabL has an approximate molecular mass of 242.5 kDa. The hemagglutinating activity was inhibited by lactose and fetuin, but was not affected by ions (Ca2+ and Mg2+). GaBL is classified as a thermostable protein because it remained active at between 30 ° C-120 ° C for 30 minutes as well as between pH 5.0-10.0 with better activity at a temperature below 60 ° C and pH 5.0. Circular dichroism of GaBL demonstrated the presence of high β-sheet content and conformational stability over a wide range of ph (4.0-11.0). The purified lectin was submitted to the antifungal test and showed potent activity against pathogenic yeasts, presenting a MIC of 12.5 and 25 μg / mL against Cryptococcos neoformans and Candida albicans. In the cytotoxic GaBL test it was not shown to be toxic to cell lines of 3T3 fibroblasts at concentrations below 50μg/mL. With this we can highlight that GaBL is a strong antifungal application with potential potential against tumor cells.